2014
DOI: 10.1002/2014jd021476
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low‐level jets along the north coast of China in summer

Abstract: A data set obtained from wind-profile radars located along the north coast of China in summer was used to compare the characteristics of the low-level jets (LLJs) at two different sites, Tianjin and Shanghai. In this paper, the characteristics and evolutions of the low-level jets were investigated, and the inertial oscillations were analyzed by the Hilbert-Huang transform technique. The results showed that LLJs (≤14 m s À1 ) dominate at both Tianjin and Shanghai, with percentages of 76.5% and 84.8%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 51 publications
1
22
0
3
Order By: Relevance
“…This basic detection method defines the LLJs by examining the horizontal wind maximum vertically, without considering the associated generation mechanism. These criteria were widely used or adopted in later literature (Doubler et al, 2015;Du et al, 2014;Miao et al, 2018;Pham et al, 2008;Wei et al, 2014;Whiteman et al, 1997;Wu & Raman, 1998). The threshold values vary due to the strength, distribution, and background circulation of LLJs.…”
Section: Identification Criteria Of Lljsmentioning
confidence: 99%
“…This basic detection method defines the LLJs by examining the horizontal wind maximum vertically, without considering the associated generation mechanism. These criteria were widely used or adopted in later literature (Doubler et al, 2015;Du et al, 2014;Miao et al, 2018;Pham et al, 2008;Wei et al, 2014;Whiteman et al, 1997;Wu & Raman, 1998). The threshold values vary due to the strength, distribution, and background circulation of LLJs.…”
Section: Identification Criteria Of Lljsmentioning
confidence: 99%
“…6 indicate that the wind shear associated with the LLJ 'nose' may play an important part in the generation and transport of turbulence in the ABL. Previous study (Wei et al, 2014) has revealed that the LLJ is a common phenomenon in Tianjin region, due to the combined effects of plain terrain for inertial oscillation (Lundquist, 2003) and strong baroclinicity related to the land-sea temperature contrast offshore (Parish, 2000). In addition, the reduced convection in winter is helpful to maintain the LLJs even during the daytime.…”
Section: Mechanism and Transport Of Intermittencymentioning
confidence: 94%
“…The quality of wind profiler measurements was strictly controlled following the procedures proposed by Wei et al (). In particular, the wind speed measurements of every two continuous levels of every day have been checked as a whole, and the wind speed measurements deviated from the mean value by more than 2 standard deviations were discarded.…”
Section: Methodsmentioning
confidence: 99%
“…The wind profilers deployed in Beijing and Guangzhou are the CFL-16 profiler, produced by the China Aerospace Science and Industry Corporation (Table 1), which provide 25 levels of wind speed and direction below~3 km AGL with a vertical resolution of 120 m, which observe the atmosphere at 6 min intervals. The wind profiler measurements collected in The quality of wind profiler measurements was strictly controlled following the procedures proposed by Wei et al (2014). In particular, the wind speed measurements of every two continuous levels of every day have been checked as a whole, and the wind speed measurements deviated from the mean value by more than 2 standard deviations were discarded.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation